Assessment of Carotid Artery Calcifications on Digital Panoramic Radiographs and Their Relationship With Periodontal Condition and Cardiovascular Risk Factors - Mehtap Bilgin Çetin; Yasemin Sezgin; Mediha Nur Nisanci Yilmaz; Cansu Köseoğlu Seçgin (Elsevier, 2021)
Objective: The main purpose of this study is to determine the presence of carotid artery calcification (CAC) detected on digital panoramic radiographs (DPRs) retrospectively and correlate the findings with cardiovascular risk factors including gender, age, smoking status, hypertension, diabetes, and hyperlipidemia, along with atherosclerotic cardiovascular disease and periodontal status. Methods: This clinical study is registered at ClinicalTrials.gov as NCT04017078. DPRs, periodontal status and cardiovascular risk factors of 1,101 patients (576 males, 525 females) were evaluated. The patients were grouped based on whether CAC was detected in dental DPRs [CAC (+)] or not [CAC (-)]. Periodontal status was categorised as gingivitis, periodontitis, and gingivitis with reduced periodontium (periodontally stable patient). Results: Out of 1,101 patients, whose mean age was 42.1 ± 15.5 years and 525 (47.7%) were female, 34 (3.1%) were diagnosed with CAC on DPRs. No significant difference was observed between groups considering gender, hypertension, diabetes, hyperlipidemia, smoking, and periodontal status. Patients aged 40-55 years (n = 398, 36.15%) and patients older than 55 years (n = 222, 20.16%) were associated with CAC (odds ratio = 4.49, 95% confidence interval = 1.65-12.17, P = 0.003; odds ratio = 4.41, 95% confidence interval = 1.33-14.61, P = 0.015, respectively). Conclusion: Among all parameters, only age exhibited significant correlation with an increased risk of carotid calcification. Further studies with prospective designs and larger study populations are needed.